What's in a number, really? - Abd Razak, Dzulkifli (2009)
WHAT is the cap for the number of SPM subjects a student can take? Sounds easy, but not quite, unless there is a context of purpose. A recent book entitled Norman Bethune by Adrienne Clarkson may be a good start. Norman who? A perfectly legitimate question since he was virtually unknown even in his hometown during his time. Not exactly a star student perhaps. This year is 70 years since Henry Norman Bethune died in China while serving the Chinese Communists in their war against Japan at the age of 49. Born an average Canadian, he had his early education in Ontario. He enrolled at the University of Toronto in 1909. Scoring top grades may not have been the inthing then. Passion was.